2022
DOI: 10.31083/j.fbl2711308
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Cyanidin-3-O-Glucoside and Verbascoside in an in Vitro Model of Diabetic Retinopathy

Abstract: Background: Reactive oxygen species (ROS) accumulation plays a pivotal role in the onset of cell damage induced by hyperglycemia and represents one of the major factors in the pathogenesis of diabetic retinopathy. In this study, we tested the antioxidants cyanidin-3-O-glucoside (C3G) and verbascoside (Verb) in the protection of retinal endothelium against glucose toxicity "in vitro". Methods: Increasing amounts (5-50 µM) of C3G, Verb or the combination of both compounds were tested in Human Retinal Endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Similarly, in human retinal endothelial cells treated with a high dosage of glucose, VB in the cells culture media at 50 µM can decrease the amount of ROS by 25% [31]. Moreover, the antioxidant activity of natural extracts containing VB (485 mg/100 g dry weight) was also dependent on its ability in chelate metal ions [32].…”
Section: Antioxidant Activitymentioning
confidence: 97%
“…Similarly, in human retinal endothelial cells treated with a high dosage of glucose, VB in the cells culture media at 50 µM can decrease the amount of ROS by 25% [31]. Moreover, the antioxidant activity of natural extracts containing VB (485 mg/100 g dry weight) was also dependent on its ability in chelate metal ions [32].…”
Section: Antioxidant Activitymentioning
confidence: 97%
“…Cyanidin-3-glucoside (C3G), also called chrysanthemin, is one of the most widely distributed anthocyanins found in nature. Similar to BRAs, C3G showed protective effects in in vivo and in vitro models of DR but gained more attention for its relative stability and easier absorbance [ 106 , 107 , 108 ]. Molecular docking analysis revealed that C3G could combine well with 78-kDa glucose-regulated protein (GRP78), a major endoplasmic reticulum (ER) chaperone protein, hence regulating ER stress [ 105 , 109 ].…”
Section: Nutraceuticalsmentioning
confidence: 99%